Enhancing the quality of life by maintaining the cultural values and vernacular functional spatial features of Malay vernacular residences - GhaffarianHoseini, AmirHosein; Ibrahim, Rahinah; Dahlan, Nur Dalilah; Baharuddin, Mohd Nasir (2010)
The quality of contemporary residential functional spaces has been mostly based on style and modernity rather than the tradition of particular regional context. This has led to new buildings which are not based on the tradition of their own regional context. In view of the rapid modernization of Malaysia, the kampong house as a Malay vernacular architecture has been replaced by modern architecture. We are motivated to conduct this study because we observed the increasing loss of functional spatial features of kampong houses and their cultural values that support Malay local quality of life. The functional spatial features include spatial characteristics of functions and spaces that are based on local needs while the cultural values represent the local way of life. We posit that the loss of functional spatial features and cultural values is key to the diminishing quality of life for people living in contemporary houses. In this research, the vernacular architectural features of kampong houses representing Malay vernacular houses are studied using archival search. We use text analysis for analyzing the cultural meanings of vernacular functional spaces and their functional spatial features. The vernacular functional spatial features are the socio-cultural or environmental characteristics of a local region in a functional space. On the other hand, the cultural meaning of functional spaces is the value that represents the resident’s local way of life in a functional space. The analysis determines the vernacular functional spatial features and cultural meanings of the functional spaces of Malay houses which represent the local needs. This study theorizes that the vernacular functional spatial features and the cultural meanings of functional spaces within Malay houses are influential in enhancing the quality of life. Correspondingly, the research found that the vernacular functional spatial features and their cultural values could support the quality of life while integrated successfully into contemporary functional spaces. Consequently, these features when utilized in designing contemporary functional spaces could exude the Malay local quality of life. In conclusion, the cultural values and functional spatial features of Malay vernacular functional spaces can be considered in contemporary residential design for enhancing the Malay quality of life in urban area.